High-frequency SAW filter based on c-BN / Al1-xScxN laminated structure and preparation method thereof
The c-BN/Al1-xScxN layered structure addresses the reliability and frequency limitations of high-frequency SAW filters by combining high propagation speed and thermal conductivity with improved piezoelectric properties, enhancing mechanical and electrical coupling for stable high-frequency performance.
Patent Information
- Application Number
- CN202510163053.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-07-11
AI Technical Summary
Existing high-frequency SAW filters face challenges in achieving reliable performance due to the unreliability of nano-sized IDT features and the limitations of current pressure materials, such as ZnO, AlN, and LiNbO3, which hinder the development of stable and high-frequency SAW filters.
A c-BN/Al1-xScxN layered structure is used, comprising a c-BN layer and an Al1-xScxN pressure material layer, which are grown using magnetron sputtering and rapid thermal annealing, to create a high-frequency SAW filter with improved mechanical and electrical coupling, stability, and reduced frequency temperature coefficient.
The c-BN/Al1-xScxN structure enhances the mechanical and electrical coupling of the SAW filter, providing high-frequency performance and stability by leveraging the high propagation speed and thermal conductivity of c-BN, while Al1-xScxN improves the piezoelectric coefficient, resulting in improved filter performance.
Smart Images

Figure CN120301394A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor technology, and particularly relates to a high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure and a preparation method thereof. Background Art
[0002] In recent years, mobile communication has developed rapidly. Filters are an important part of this field, and the miniaturization and high-frequencyization of filter devices have become the development direction of mobile communication devices. Therefore, how to increase the center frequency of devices is the key to the further development of the current mobile communication field.
[0003] Since communication in the low-frequency band is gradually becoming congested, high-frequencyization is the development trend of current communication technology, which makes high-frequency and high-power SAW (Surface Acoustic Wave) filters more and more popular. Piezoelectric materials are important carriers for converting energy and transmitting signals in SAW filters. The propagation speed of SAWs determines the center frequency of SAW filters, and the stronger the piezoelectric performance of the material, the greater the change in the propagation speed of SAWs. That is to say, to realize a high-frequency SAW filter, a piezoelectric material capable of increasing the propagation speed is required. The electromechanical coupling coefficient K 2 is the main parameter for measuring the performance of piezoelectric materials, which characterizes the conversion efficiency between electrical energy and mechanical energy. The frequency temperature coefficient reflects the degree of change in the performance of piezoelectric materials with temperature and reflects the stability of the performance of piezoelectric materials. Therefore, the core of preparing a high-frequency SAW filter lies in the characteristics of piezoelectric materials and their crystallization quality.
[0004] In the prior art, in order to increase the center frequency, the IDT feature size can be reduced during the preparation of high-frequency SAW devices. However, the reliability of the IDT (Inter Digital Transducers) with nano feature sizes in high-frequency SAW devices cannot be guaranteed. On the other hand, substrate materials and piezoelectric materials with high sound velocities can also be used. Common piezoelectric materials include ZnO, AlN, LiNbO3, etc. Among them, the electromechanical coupling coefficient of ZnO is 3.2%, the dielectric constant is 9.9, but the propagation speed is only 2800 m / s, which is not conducive to the preparation of SAW filters. LiNbO3 is not easy to grow in the form of a thin film compared with ZnO and AlN. AlN thin film materials with a certain preferred orientation also have their disadvantages, that is, the frequency temperature coefficient is relatively large, which is 3.9×10 -6 / °C, which is not conducive to the stability of SAW devices. Summary of the Invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a c-BN / Al-based1-x Sc x High-frequency SAW filter with N-layer structure and its preparation method. The technical problem to be solved by the present invention is realized through the following technical solutions:
[0006] In the first aspect, the present invention provides a high-frequency SAW filter based on c-BN / Al 1-x Sc x N-layer structure, comprising:
[0007] A substrate;
[0008] A c-BN / Al 1-x Sc x N-layer structure located on the surface of the substrate, and the c-BN / Al 1-x Sc x N-layer structure includes a c-BN layer and an Al 1-x Sc x N piezoelectric material layer from bottom to top, where x represents the component of Sc;
[0009] An electrode layer located on the surface of the c-BN / Al 1-x Sc x N-layer structure.
[0010] In an embodiment of the present invention, 0.2 ≤ x ≤ 0.43.
[0011] In an embodiment of the present invention, the substrate is a silicon substrate or an Al2O3 substrate.
[0012] In an embodiment of the present invention, in the direction perpendicular to the plane of the substrate, the thickness of the c-BN layer is the same as that of the Al 1-x Sc x N piezoelectric material layer.
[0013] In an embodiment of the present invention, the thickness of the c-BN layer is 80 - 150 nm, and the thickness of the Al 1-x Sc x N piezoelectric material layer is 80 - 150 nm.
[0014] In an embodiment of the present invention, the frequency temperature coefficient of the c-BN / Al 1-x Sc x N-layer structure is lower than 1×10 -6 / K, and the phase velocity is greater than 8000 m / s.
[0015] In the second aspect, the present invention also provides a preparation method for a high-frequency SAW filter based on c-BN / Al 1-x Sc x N-layer structure, including:
[0016] Provide a substrate;
[0017] Use magnetron sputtering to grow a c-BN layer on the surface of the substrate, and perform rapid thermal annealing on the sample after growing the c-BN layer;
[0018] Use magnetron sputtering to grow Al 1-x Sc x N piezoelectric material layer, and perform rapid thermal annealing on the sample after growing the Al 1-x Sc x N piezoelectric material layer to form a c-BN / Al 1-x Sc x N laminated structure;
[0019] Grow an electrode layer on the surface of the c-BN / Al 1-x Sc x N laminated structure.
[0020] In an embodiment of the present invention, the step of using magnetron sputtering to grow a c-BN layer on the surface of the substrate and performing rapid thermal annealing on the sample after growing the c-BN layer includes:
[0021] Place the cleaned substrate in the magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10 -5 Pa, introduce nitrogen and argon with a volume ratio of 1:3;
[0022] Perform pre-sputtering to remove impurities on the surface of the BN ceramic target, then heat up to 675°C, use the BN ceramic target as the sputtering target and start sputtering to form a c-BN layer;
[0023] Put the sample after growing the c-BN layer into the annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 -3 Pa, perform rapid thermal annealing treatment under the conditions of an annealing temperature of 900°C, an annealing time of 60 s, a gradient heating rate of 10°C / s, and 800 sccm of nitrogen.
[0024] In an embodiment of the present invention, the step of using magnetron sputtering to grow an Al 1-x Sc x N piezoelectric material layer on the surface of the c-BN layer and performing rapid thermal annealing on the sample after growing the Al 1-x Sc x N piezoelectric material layer to form a c-BN / Al 1-x Sc x N laminated structure includes:
[0025] Place the sample after growing the c-BN layer in the magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10-5 After reaching 1 Pa, nitrogen and argon with a volume ratio of 1:1.5 are introduced.
[0026] After the gas flow rate is stable, pre-sputtering is carried out to remove impurities on the surfaces of the pure aluminum metal target and the pure scandium metal target.
[0027] Heat up to 450 °C, use the pure aluminum metal target and the pure scandium metal target as sputtering targets and start sputtering to form an Al 1-x Sc x N piezoelectric material layer;
[0028] Put the sample after growing the Al 1-x Sc x N piezoelectric material layer into an annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 -3 Pa, rapid thermal annealing treatment is carried out under the conditions of an annealing temperature of 700 °C, an annealing time of 300 s, a gradient heating rate of 10 °C / s, and 800 sccm of nitrogen to form a c-BN / Al 1-x Sc x N laminated structure.
[0029] In an embodiment of the present invention, the step of growing an electrode layer on the surface of the c-BN / Al 1-x Sc x N laminated structure includes:
[0030] Using an electron beam evaporation process to deposit the metal Au on the surface of the c-BN / Al 1-x Sc x N laminated structure to form an electrode layer.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] The present invention provides a high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure and a preparation method thereof. The SAW filter includes a laminated structure formed by a c-BN layer and an Al 1-x Sc x N piezoelectric material layer. Since c-BN has a very high propagation speed and thermal conductivity, and has a low frequency temperature coefficient, it is beneficial to the realization of the stability and high-frequency performance of the SAW filter. At the same time, Al 1-x Sc x N can increase the piezoelectric coefficient, and thus increase the electromechanical coupling coefficient of the SAW filter.
[0033] In addition, since the Al 1-x Sc x N piezoelectric material layer and the c-BN layer also have complementary piezoelectric characteristics and similar lattice structures, which also ensures that Al1-x Sc x High-quality crystal growth of N.
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. Description of the Drawings
[0035] Figure 1 is a schematic structural diagram of a high-frequency SAW filter based on a c-BN / Al 1-x Sc x ScN laminated structure provided by an embodiment of the present invention;
[0036] Figure 2 is a flowchart of a preparation method of a high-frequency SAW filter based on a c-BN / Al 1-x Sc x ScN laminated structure provided by an embodiment of the present invention. Detailed Embodiments
[0037] The present invention will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0038] Figure 1 is a schematic structural diagram of a high-frequency SAW filter based on a c-BN / Al 1-x Sc x ScN laminated structure provided by an embodiment of the present invention. Please refer to Figure 1 According to an embodiment of the present invention, a high-frequency SAW filter based on a c-BN / Al 1-x Sc x ScN laminated structure includes:
[0039] Substrate 1;
[0040] A c-BN / Al 1-x Sc x ScN laminated structure 2 located on the surface of substrate 1, and the c-BN / Al 1-x Sc x ScN laminated structure 2 includes a c-BN layer 201 and an Al 1-x Sc x ScN piezoelectric material layer 202 from bottom to top, where x represents the component of Sc;
[0041] An electrode layer 3 located on the surface of the c-BN / Al 1-x Sc x ScN laminated structure 2.
[0042] In this embodiment, the c-BN layer 201 and the Al 1-x Sc xThe N piezoelectric material layer 202 forms a laminated structure 2, which together serves as the piezoelectric material. On the one hand, the propagation speed of c-BN is 10642 m / s and the thermal conductivity is 13 W / (cm·K). Compared with other piezoelectric materials, it has a very high propagation speed and thermal conductivity, and the frequency temperature coefficient of c-BN is only 0.1×10 -6 / ℃. Therefore, introducing the c-BN layer 201 is beneficial to the realization of the stability and high-frequency performance of the SAW filter. However, on the other hand, c-BN also has deficiencies, that is, the electromechanical coupling coefficient is relatively low, only 0.54%, which is not conducive to the conversion of mechanical energy and electrical energy in the SAW filter. During the research process, the inventor found that Al 1-x Sc x N can improve the electromechanical coupling coefficient of the SAW filter. Therefore, an Al 1-x Sc x N piezoelectric material layer 202 is further grown on the surface of the c-BN layer 201. By combining the high propagation speed of the c-BN layer 201 with the high electromechanical coupling coefficient of the Al 1-x Sc x N piezoelectric material layer 202, the center frequency of the SAW filter is improved.
[0043] In addition, the thermal conductivity of c-BN is much higher than that of AlN and AlScN, which can enable the high-frequency SAW device to dissipate heat better and faster. Since the Al 1-x Sc x N piezoelectric material layer 202 and the c-BN layer 201 also have complementary piezoelectric characteristics and similar lattice structures, which also ensure the high-quality crystalline growth of Al 1-x Sc x N.
[0044] Those skilled in the art should understand that since the surface acoustic wave propagation speed of diamond is greater than 10000 m / s, which has the highest propagation speed and the highest thermal conductivity among known materials, it is beneficial to improve the center frequency and stability of the SAW filter. Therefore, in order to improve the center frequency of the SAW filter, diamond substrates 1 are generally selected in the prior art, and AlN or AlScN thin films are grown on their surfaces. However, diamond has a high cost, and it is relatively difficult to prepare AlN or AlScN thin films using diamond as the substrate 1, and a buffer layer needs to be deposited first. In view of this, in this embodiment, an Al2O3 substrate or a silicon substrate is selectively used.
[0045] Specifically, since c-BN also has a very high surface acoustic wave propagation speed, and is low in cost and easy to prepare, combined with the Al2O3 substrate 1 or the silicon substrate 1 on this basis, it can reduce the cost and simplify the preparation process while ensuring the device performance.
[0046] In addition, c-BN and Al 1-x Scx All N belong to the III-V nitride system, are compatible with semiconductor process technologies, and can be fabricated on various substrates 1.
[0047] Furthermore, doping a high content of Sc element in AlN (AlScN) can enhance the piezoelectric coefficient, thereby improving the electromechanical coupling coefficient of the SAW filter. Optionally, 1-x Sc x The value range of the component x of the Sc element in the AlScN piezoelectric material layer 202 is: 0.2 ≤ x ≤ 0.43. In this way, while enhancing the piezoelectric coefficient, it is possible to avoid a decrease in the Young's modulus of the material due to 1-x Sc x an excessively high concentration of the Sc element in AlScN, which will have an adverse effect on the propagation speed.
[0048] Optionally, in the direction perpendicular to the plane of the substrate 1, the thickness of the c-BN layer 201 is the same as that of the 1-x Sc x AlScN piezoelectric material layer 202. Among them, the thickness of the c-BN layer 201 is 80 - 150 nm, and the 1-x Sc x thickness of the AlScN piezoelectric material layer 202 is 80 - 150 nm.
[0049] Optionally, the frequency temperature coefficient of the c-BN / Al 1-x Sc x AlScN stacked structure 2 is lower than 1×10 -6 / K, and the phase velocity is greater than 8000 m / s.
[0050] Figure 2 is a flowchart of a method for fabricating a high-frequency SAW filter based on the c-BN / Al 1-x Sc x AlScN stacked structure. Please refer to Figures 1 - 2 , and an embodiment of the present invention also provides a method for fabricating a high-frequency SAW filter based on the c-BN / Al 1-x Sc x AlScN stacked structure 2, including:
[0051] S1. Provide a substrate 1.
[0052] Specifically, taking the Al2O3 substrate 1 as an example, the Al2O3 substrate 1 is a single wafer with single-sided polishing and a roughness less than 0.3 nm. First, fix the Al2O3 substrate 1 on the cleaning rack, and then sequentially place it into acetone, ethanol, and deionized water for ultrasonic cleaning for 10 - 15 min. The ultrasonic frequency is set to 80 - 100 w. Then, dry the Al2O3 substrate 1 that has undergone surface ultrasonic cleaning with a nitrogen gun. After cleaning through the above steps, dust, organic impurities, etc. on the sample surface can be removed.
[0053] S2. Use magnetron sputtering to grow a c-BN layer 201 on the surface of the substrate 1, and perform rapid thermal annealing on the sample after growing the c-BN layer 201.
[0054] It should be noted that before growing the c-BN layer 201 on the surface of the Al2O3 substrate 1, the Al2O3 substrate 1 can be pretreated. Specifically, place the Al2O3 substrate 1 in the magnetron sputtering chamber, and use the ion bombardment method to remove the pollutants on the surface of the Al2O3 substrate 1. The conditions are: radio frequency power is 50 W, argon gas flow rate is 64 sccm, and the duration is 300 s.
[0055] Optionally, in step S2, the steps of using magnetron sputtering to grow a c-BN layer 201 on the surface of the substrate 1 and performing rapid thermal annealing on the sample after growing the c-BN layer 201 include:
[0056] S201. Place the cleaned substrate 1 in the magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10 -5 Pa, introduce nitrogen and argon with a volume ratio of 1:3.
[0057] S202. Perform pre-sputtering to remove impurities on the surface of the BN ceramic target, then heat up to 675 °C, use the BN ceramic target as the sputtering target and start sputtering to form a c-BN layer 201.
[0058] S203. Place the sample after growing the c-BN layer 201 into the annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 - 3 Pa, perform rapid thermal annealing treatment under the conditions of an annealing temperature of 900 °C, an annealing time of 60 s, a gradient heating rate of 10 °C / s, and 800 sccm nitrogen.
[0059] Optionally, use a BN ceramic target with a purity of 99.999% as the sputtering target for growing the c-BN layer 201, and use radio frequency source sputtering for growth. Specifically, in steps S201 - S202, place the Al2O3 substrate 1 in the magnetron sputtering chamber. After the vacuum degree reaches 1×10 -5After reaching 1 Pa, introduce high-purity nitrogen and high-purity argon with a volume ratio of 1:3. After the gas flow rate stabilizes, set the sputtering power of the target. The power range of the BN ceramic target is 90 - 120 W. After pre-sputtering the BN ceramic target, heat up to 675 °C and start sputtering the c-BN layer 201 for 60 minutes.
[0060] S3. Use magnetron sputtering to grow Al 1-x Sc x N piezoelectric material layer 202 on the surface of the c-BN layer 201. After growing the Al 1- x Sc x N piezoelectric material layer 202, perform rapid thermal annealing on the sample to form a c-BN / Al 1-x Sc x N laminated structure 2.
[0061] Optionally, in step S3, use magnetron sputtering to grow Al 1-x Sc x N piezoelectric material layer 202 on the surface of the c-BN layer 201. After growing the Al 1-x Sc x N piezoelectric material layer 202, perform rapid thermal annealing on the sample to form a c-BN / Al 1-x Sc x N laminated structure 2, the steps include:
[0062] S301. Place the sample with the c-BN layer 201 grown in the magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10 -5 Pa, introduce nitrogen and argon with a volume ratio of 1:1.5;
[0063] S302. After the gas flow rate stabilizes, perform pre-sputtering to remove impurities on the surfaces of the pure aluminum metal target and the pure scandium metal target;
[0064] S303. Heat up to 450 °C, use the pure aluminum metal target and the pure scandium metal target as sputtering targets and start sputtering to form Al 1-x Sc x N piezoelectric material layer 202;
[0065] S304. Place the sample with the Al 1-x Sc x N piezoelectric material layer 202 grown in an annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 -3 Pa, perform rapid thermal annealing treatment under the conditions of an annealing temperature of 700 °C, an annealing time of 300 s, a temperature increase gradient of 10 °C / s, and 800 sccm nitrogen to form a c-BN / Al 1-x Sc x N laminated structure 2.
[0066] Specifically, in steps S301 to S304, a pure aluminum metal target with a purity of 99.999% and a pure scandium (Sc) metal target with a purity of 99.999% are used as sputtering targets for growing the Al 1-x Sc x N piezoelectric material layer 202. Among them, the pure aluminum metal target uses a DC source, and the pure scandium metal target uses an RF source. After cleaning the sample deposited with the c-BN layer 201, it is placed in a magnetron sputtering chamber. After the vacuum degree reaches 1×10 -5 Pa, high-purity nitrogen and high-purity argon with a volume ratio of 1:1.5 are introduced. After the gas flow rate is stable, the sputtering power of the two targets is set. Exemplarily, the power range of the pure aluminum metal target is 120 - 160 w, and the power range of the pure scandium metal target is 90 - 130 W. The pure aluminum metal target and the pure scandium metal target are pre-sputtered respectively, and the temperature is raised to 450 °C, and then the sputtering of the Al 1-x Sc x N piezoelectric material layer 202 is started, and the sputtering duration is 60 min.
[0067] S4. Growing an electrode layer 3 on the surface of the c-BN / Al 1-x Sc x N laminated structure 2.
[0068] Optionally, in step S4, the step of growing the electrode layer 3 on the surface of the c-BN / Al 1-x Sc x N laminated structure 2 includes: depositing the metal Au on the surface of the c-BN / Al 1-x Sc x N laminated structure 2 by using an electron beam evaporation process to form the electrode layer 3.
[0069] Specifically, the sample with the grown c-BN / Al 1-x Sc x N laminated structure 2 is attached to a mask plate and placed in a tray, and then sent into a vacuum reaction chamber, and evaporated for 2 - 3 h under the conditions of a pressure of 3×10 -5 Pa and a power of 200 W.
[0070] It can be seen that in the preparation method of the high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure provided by the present invention, the film-forming methods such as the magnetron sputtering method and the electron beam evaporation method involved are all common methods in the semiconductor CMOS process, can be effectively integrated with the existing CMOS process, can effectively reduce the production cost on the basis of ensuring excellent device performance, and conform to the development law of Moore's Law; and the preparation process involved is simple, the material cost is low, and the preparation process is environmentally friendly and safe.
[0071] As can be seen from the above embodiments, the beneficial effects of the present invention are as follows:
[0072] The present invention provides a high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure and a preparation method thereof. The SAW filter includes a laminated structure formed by a c-BN layer and an Al 1-x Sc x N piezoelectric material layer. Since c-BN has a very high propagation speed and thermal conductivity, and has a low frequency temperature coefficient, it is beneficial to the realization of the stability and high-frequency performance of the SAW filter. At the same time, Al 1-x Sc x N can increase the piezoelectric coefficient, thereby increasing the electromechanical coupling coefficient of the SAW filter.
[0073] In addition, since the Al 1-x Sc x N piezoelectric material layer and the c-BN layer also have complementary piezoelectric characteristics and similar lattice structures, which also ensure the high-quality crystal growth of Al 1-x Sc x N.
[0074] In the description of the present invention, it should be understood that the descriptions referring to terms such as "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification.
[0075] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or substitutions can still be made, and all should be regarded as belonging to the protection scope of the present invention.
Claims
1. A high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure, characterized in that Comprising: A substrate; c-BN / Al located on the surface of the substrate 1-x Sc x ScN laminate structure, where the c-BN / Al 1-x Sc x ScN laminate structure includes a c-BN layer and an Al 1-x Sc x ScN piezoelectric material layer from bottom to top, where x represents the component of Sc; Located on the surface of the c-BN / Al 1-x Sc x electrode layer of the N stacked structure.
2. The high-frequency SAW filter based on the c-BN / Al 1-x Sc x N stacked structure, characterized in that 0.2≤x≤0.43。 3. The high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that The substrate is a silicon substrate or an Al2O3 substrate.
4. The high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that In a direction perpendicular to the plane of the substrate, the thickness of the c-BN layer is the same as that of the Al 1-x Sc x N piezoelectric material layer.
5. The high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that The thickness of the c-BN layer is 80 to 150 nm, and the 1-x Sc x thickness of the AlN piezoelectric material layer is 80 to 150 nm.
6. The high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that The c-BN / Al 1-x Sc x The frequency temperature coefficient of the N stacked structure is lower than 1×10 -6 / K, and the phase velocity is greater than 8000 m / s.
7. A preparation method of a high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure, characterized in that Comprising: Providing a substrate; Growing a c-BN layer on the surface of the substrate by magnetron sputtering, and performing rapid thermal annealing on the sample after growing the c-BN layer; Growing Al on the surface of the c-BN layer by magnetron sputtering 1-x Sc x N piezoelectric material layer, and performing rapid thermal annealing on the sample after growing the Al 1-x Sc x N piezoelectric material layer to form a c-BN / Al 1-x Sc x N laminated structure; On the surface of the c-BN / Al 1-x Sc x A surface of the N stacked structure grows an electrode layer.
8. The preparation method of the high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that The step of growing a c-BN layer on the surface of the substrate by magnetron sputtering and performing rapid thermal annealing on the sample after growing the c-BN layer includes: Place the cleaned substrate in the magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10 -5 Pa, introduce nitrogen and argon with a volume ratio of 1:3; Performing pre-sputtering to remove impurities on the surface of the BN ceramic target, then heating to 675 °C, using the BN ceramic target as a sputtering target and starting sputtering to form a c-BN layer; Put the sample after growing the c-BN layer into an annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 -3 Pa, perform rapid thermal annealing treatment under the conditions of an annealing temperature of 900 °C, an annealing time of 60 s, a gradient heating rate of 10 °C / s, and 800 sccm of nitrogen gas.
9. The preparation method of the high-frequency SAW filter based on the c-BN / Al 1-x Sc x N laminated structure, characterized in that Growing Al on the surface of the c-BN layer by magnetron sputtering 1-x Sc x N piezoelectric material layer, and performing rapid thermal annealing on the sample after growing the Al 1-x Sc x N piezoelectric material layer to form the steps of a c-BN / Al 1-x Sc x N laminated structure Comprising: Place the sample for growing the c-BN layer in a magnetron sputtering chamber. After the vacuum degree of the magnetron sputtering chamber reaches 1×10 -5 Pa, introduce nitrogen and argon with a volume ratio of 1:1.5; Performing pre-sputtering to remove impurities on the surfaces of the pure aluminum metal target and the pure scandium metal target after the gas flow is stable; Heat up to 450 °C, use pure aluminum metal target and pure scandium metal target as sputtering targets and start sputtering to form an Al 1- x Sc x N piezoelectric material layer; After growing the Al 1-x Sc x N piezoelectric material layer, place the sample in an annealing furnace. After the vacuum degree in the annealing furnace reaches 1×10 - 3 Pa, perform rapid thermal annealing treatment under the conditions of an annealing temperature of 700 °C, an annealing time of 300 s, a temperature increase gradient of 10 °C / s, and 800 sccm of nitrogen gas to form a c-BN / Al 1-x Sc x N laminated structure.
10. The preparation method of a high-frequency SAW filter based on a c-BN / Al 1-x Sc x N laminated structure, characterized in that On the c-BN / Al 1-x Sc x The step of growing an electrode layer on the surface of the ScN stacked structure includes: Deposit metal Au on the surface of the c-BN / Al 1-x Sc x N laminated structure to form an electrode layer.